CASE PRESENTATION OF 55-YEAR-OLD MAN WITH ACUTE MYELOID LEUKEMIA AND COVID 19 - Novita Fajar Sari; Herniah Asti Wulanjani; Ardhea Jaludamascena; Dwi Retnoningrum (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Acute myeloid leukemia (AML) is a malignancy originating from multipotential hematopoietic cells, which is characterized by clonal proliferation of abnormal blast cells in the bone marrow and failure of normal cell production. Coronavirus disease-19 (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. COVID-19 infection in AML patients will affect laboratory examinations to support the diagnosis of COVID-19 and the patient's prognosis. Case presentation: A 55-year- old man went to the hospital for chemotherapy and diagnosed of acute myelomonocytic leukemia. Patient complains of his gingival bleeding. The results of the routine haematological examination showed pancytopenia and the patient requires blood transfusion before chemotherapy. On the third day of treatment, the patient complained of fever, after several day patient complained cough, and shortness of breath. Physical examination showed pulse 100x/minutes, respiratory rate 26x/minutes, temperature 39.8˚C, crackles of the lungs. RT-PCR examination from nasopharyngeal swab showed a positive SARS-CoV-2. During treatment, the laboratory tests showed pancytopenia, increased D-Dimer, C-reactive protein, ferritin and procalcitonin. After the 42th day of treatment, the patient had clinical improvement, the fifth evaluation swab showed a negative RT-PCR result. Conclusion: AML patients have a higher risk of infection, especially COVID-19 infection. Correct laboratory examinations and treatment will promote a better prognosis. It is necessary to educate leukemic patients so that they always take precautions against infection, especially the prevention of COVID-19.